Margaret Kilpinen Pianisti, pedagogi, puoliso - Rahkonen, Margit (Tietolipas, 2023)
The biography of Margaret Darling Kilpinen (1896-1965) represents the fields of music history and women's studies. It brings forth a woman who is of pliable but also strong character. She was active for over four decades in the musical life of Finland. What kind of professional role, combining performing and pedagogical work, was she able to build for herself? She was the wife of a well-known, strong-willed composer who had many ties to Germany, and also the mother of a daughter. How was she able to keep up her own artistry? The book deals with Margaret's role as a solo and lied pianist, her long career as a pedagogue in the Sibelius Academy and as a harpsichord player with a part in the rise of old music in Finland in the 1930s. There is also the microhistorical angle: While looking at Margaret as a person and her life, general tendencies and attitudes among the cultural circles of Finland of her time are revealed. The main source material for the book, which is available for use for the very first time, has been the correspondence between Yrjö and Margaret Kilpinen.